ANALISIS PENGEMBANGAN JARINGAN PERPIPAAN DAN RENCANA ANGGARAN BIAYA DI DESA PASLATEN KABUPATEN MINAHASA SELATAN - Rifka Lumintang; Nicky Rampengan; Titof Tulaka (Sustainable Construction (SUSCON), 2024)
The Drinking Water Supply System (SPAM), based on Government Regulation No. 16 of 2005 and Technical Standards from the Directorate General of Spatial Planning regarding Urban or Rural Clean Water Development, is an integrated system primarily focused on providing drinking water for household consumption, sourced from the supply of Regional Water Company (PDAM). This research focuses on data collection and field orientation through field surveys. The research location is in South Minahasa Regency, Tatapaan District, Paslaten Village. From the calculations conducted, a total of 2943.75 liters per hour is needed to meet clean water needs until 2038. The clean water distribution system relies on gravity flow methods, with a storage tank measuring 6 x 3 x 2 meters. To reach 284 households, pipes of various sizes are used, including ¾ inch, 6 inches, 4 inches, ½ inch, and 1 inch. To realize this plan, a budget of Rp. 349,728,286.00 is required.